MAF1 inhibits hepatocarcinogenesis by fostering an immunostimulatory tumor microenvironment - Di Cao; Shi-Juan Mai; Hui-yun Wang; Ge Ren; Yue-Ning Wang; Chao-Yue Sun; Haojiang Li; Yu-Feng Zhou; Mei-Yin Zhang; Shuo-Cheng Wang (Journal for ImmunoTherapy of Cancer)
Background The biological significance of MAF1, a tumor suppressor, in carcinogenesis and immune response of hepatocellular carcinoma (HCC) remains unreported. Understanding the underlying mechanisms by which MAF1 enhances anti-tumor immunity in HCC is crucial for developing novel immunotherapy strategies and enhancing clinical responses to treatment for patients with HCC.Methods Mice were subjected to hydrodynamic tail vein injections of transposon vectors to overexpress AKT/NRas, or c-Myc, with or without wild-type (WT) or mutant-activated (−4A) MAF1, or short-hairpin MAF1 (shMAF1). Liver tissues and tumors were harvested and analyzed using histology, immunohistochemistry, immunoblotting, quantitative reverse-transcription PCR, and flow cytometry. MAF1 was overexpressed or knocked down in HCC cells via lentiviral transfection. Cell lines were analyzed using RNA sequencing, immunoblotting, dual luciferase reporter, and chromatin precipitation assays.Results Both MAF1-WT and MAF1-4A proteins significantly inhibit hepatocarcinogenesis in mice, with the mutant form exhibiting a stronger suppressive effect. Although MAF1 knockdown alone does not induce abnormalities in the mouse liver, it accelerates c-Myc-induced carcinogenesis. Our results provide the first in vivo evidence that MAF1 plays a tumor suppressor role by activating PTEN to suppress the AKT-mammalian target of rapamycin signaling pathway during hepatocarcinogenesis in physiologically relevant tumor models. More importantly, we found that MAF1 not only enhances the intratumoral infiltration of CD8+ T cells by increasing CXCL10 secretion but also enhances their functional activity by inhibiting PDL1 transcription in mouse liver cancer, which were confirmed in human HCC or in vitro experiments. Furthermore, PDL1 overexpression accelerates mouse hepatocarcinogenesis by antagonizing the tumor-suppressive role of MAF1.Conclusions Our study uncovers a novel anti-tumor immunity of MAF1 in hepatocarcinogenesis and human HCC. These findings suggest that the stimulated MAF1 could potentially improve immunotherapy in combination with immune checkpoint inhibitors in HCC patients, especially in those with an absence of T cells in HCC tissues.